Atypical chronic copper poisoning in a sheep secondary to copper wire ingestion – case report Intoxicação crônica por cobre atípica em ovino pelo consumo de fios de cobre – relato de caso - Quevedo L.S.* (2022)
© 2022. Arquivo Brasileiro de Medicina Veterinaria e Zootecnia. All Rights Reserved.A 14-month-old female Texel sheep that came from a herd made up of 19 animals showed haemoglobinuria, apathy, and anorexia, and died two days after the start of the clinical signals. The sheep remained in a natural grassland, where trailers were repaired, and multiple copper wires were deposited on the pasture. The animal had tachycardia, tachypnoea, pale mucous membranes, groaning pain on abdominal palpation, circling, head pressing, intensely hemolyzed plasma, and intense azotaemia. The necropsy showed focally extensive oedema in the inguinal and medial region of pelvic limbs, kidneys dark brown, and liver diffusely yellow with an evident moderate diffuse lobular pattern. The abomasum had a considerable amount of enameled material of thickness, firm to the cut, with 1-5 mm (copper wires). Histopathological examination showed marked diffuse tubular and glomerular coagulative necrosis in the kidneys, in addition to neutrophils, macrophages, lymphocytes, and plasma cells with moderate multifocal nephritis. The liver showed centrilobular necrosis, moderate hepatocellular edema, multifocal cholestasis, and in the lungs and brain mild to moderate diffuse edema. Copper content in the frozen liver (in natura) reached 1,598 mg/kg. Copper mesh ingestion led to sheep poisoning, which in this case was considered an atypical form of chronic primary copper poisoning.